2023
DOI: 10.3389/fmicb.2023.1180018
|View full text |Cite
|
Sign up to set email alerts
|

Use of reverse osmosis concentrate for mitigating greenhouse gas emissions from pig slurry

Abstract: Due to the high global warming potential (GWP) in a short time scale (GWP100 = 28 vs. GWP20 = 86), mitigating CH4 emissions could have an early impact on reducing current global warming effects. The manure storage tank emits a significant amount of CH4, which can diminish the environmental benefit resulting from the anaerobic digestion of manure that can generate renewable energy. In the present study, we added the reverse osmosis concentrate (ROC) rich in salt to the pig slurry (PS) storage tank to reduce CH4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Studies 1, 5, 6, and 10 identified manure storage as one of the main processes that negatively impacted the environment in their research. According to Im et al [24], significant amounts of methane are emitted by manure storage tanks, which are important for maintaining the greenhouse effect.…”
Section: Discussionmentioning
confidence: 99%
“…Studies 1, 5, 6, and 10 identified manure storage as one of the main processes that negatively impacted the environment in their research. According to Im et al [24], significant amounts of methane are emitted by manure storage tanks, which are important for maintaining the greenhouse effect.…”
Section: Discussionmentioning
confidence: 99%